Bayesian estimates of the mean recharge elevations of water sources in the Central America region using stable water - Avellano, L. Nicole (2020)
Study region: Central America. Study focus: Knowledge of the mean recharge elevation (MRE) of water resources is important where water resources are vulnerable. The purpose of this study was to develop and apply a Bayesian approach which incorporates isotopic uncertainties and evaporative effects on isotopic compositions to determine the MRE of 680 surface water sources from Central America. Differences were assessed between results from our approach and those from other isotope-based methods that do not account for these factors. New hydrological insights for the region: Different MRE patterns were identified for Pacific and Caribbean basins, which were characterized by distinct isotopic signatures: 1) the Pacific slope had recharge occurring at higher elevations relative to the source mean catchment elevation (MCE) and 2) the Caribbean slope had recharge largely occurring at elevations lower than the MCE. These relationships were quantified: MREP = 1.072 (MCE) + 45.65 (Pacific: r2 = 0.93, error = 144 m); MREC = 0.9493 (MCE) – 28.24 (Caribbean: r2 = 0.83, error = 190 m). The MRE, surface water site elevation (SWSE), and MRE-SWSE differences were generally greater on the Pacific slope, which hosts most of the region’s population. Bayesian MRE estimates were on average lower than MREs obtained using other methods and may better approximate the actual (recharge-weighed) MRE, suggesting that the inclusion of isotopic uncertainties, evaporative corrections, and recharge likelihoods all positively effect MRE estimations.